Establish ASEAN-AUSTRALIA Communication In Resolving Humanitarian Issues For International Asylum Seekers and Refugees - Bakker, Felix Ferdin (Veteran Law Review, 2021)
The current problem of refugees cannot be handled with policies that address the root of the problem. The increasing number of refugees in the Southeast Asian region makes transit countries overwhelmed in dealing with this problem. On the other hand, as a refugee recipient country in the last ten years, Australia has had a strict policy in accepting refugees. Australia's approach to return refugee ships to a transit country is a controversial policy because Australia itself is a country that signed the 1951 convention on refugee status. On the other hand, the existence of refugees and asylum seekers has a significant impact on the local community's social changes, and the current refugee policy arrangement is still in the hands of UNHCR ( United Nations High Commissioner for Refugees) under the auspices of the United Nations. There has been no concrete communication to touch the root of the problem of refugees and asylum seekers. Through an enthusiastic approach and communication with community-based management between ASEAN countries and Australia, it is hoped that it can resolve human rights issues related to supervision to empower refugees in society to become citizens of a third country, in this case, Australia.